Manusia dan Kebahagiaan: Pandangan Filsafat Yunani dan Respon Syed Muhammad Naquib al-Attas - Kholili Hasib (Universitas Darussalam Gontor, 2019)
The thought of Greek Philosophers has influenced both the western and eastern scholar (Muslims), included the concept of human being. The concept of man in Islam including in metaphysic area. Syed Muhammad Naquib al Attas, the contemporary Muslim scientists who articulate the concepts of Muslim philosophers, the Sufis, and Mutakallim in themodern world. Al Attas’ concept of human being has two functions; first, as a response to the western’s thought. Second, as a base concept of Islamic psychology. Therefore, the concept of the human being toward Al-Attas is to raise the Traditional Islamic Concept in modern form and needs.